2012
DOI: 10.4103/0971-9784.91473
|View full text |Cite
|
Sign up to set email alerts
|

The effects of preemptive pregabalin on attenuation of stress response to endotracheal intubation and opioid- sparing effect in patients undergoing off-pump coronary artery bypass grafting

Abstract: The clinical study was designed to evaluate and compare single preoperative dose of pregabalin to a placebo regarding hemodynamic responses to laryngoscopy and endotracheal intubation, to assess perioperative fentanyl requirement and any side-effects. It was a randomized, double-blind, placebo-controlled, parallel assignment, efficacy study. The study was done at a tertiary university hospital. This study was a comparison between two groups of 30 adult patients scheduled for elective off pump coronary artery b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
3

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(12 citation statements)
references
References 22 publications
0
9
0
3
Order By: Relevance
“…There were 4 studies 19 22 with a total of 107 patients taking pregabalin and 110 patients on the control treatment in this group. Pregabalin reduced the pain score at rest 2 hours postsurgery ( P = 0.005).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There were 4 studies 19 22 with a total of 107 patients taking pregabalin and 110 patients on the control treatment in this group. Pregabalin reduced the pain score at rest 2 hours postsurgery ( P = 0.005).…”
Section: Resultsmentioning
confidence: 99%
“…Thirty studies had included data on the sedative effects of pregabalin, 13 , 14 , 21 , 22 , 25 , 29 , 30 , 32 , 37 , 39 , 43 , 50 52 , 55 57 , 59 , 60 , 62 , 65 69 , 77 , 79 , 82 , 85 , 87 , 88 with a total of 1147 patients taking pregabalin and 1170 patients on the control treatment. Subgroup analysis was performed on studies according to the surgical categories (number of studies) under cardiothoracic surgery (2), ENT surgery (3), gynecologic surgery (4), laparoscopic cholecystectomy (2), orthopedic surgery (7), spine surgery (6), and miscellaneous surgery (6).…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent with other studies, where it was demonstrated that pregabalin offered better sedation and anxiolysis when compared to placebo and clonidine. [ 3 13 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 2 ] Adequate premedication has been shown to attenuate this pressor response. Sundar et al .,[ 3 ] showed that the mean systolic and diastolic pressure during different time periods after intubation were significantly lower with 150 mg of pregabalin premedication compared with placebo. Gupta et al .…”
Section: Introductionmentioning
confidence: 99%
“…In other studies, the results were unstable as time to extubation was significantly longer in the pregabalin group [2, 3] or similar between groups [4, 5]. …”
mentioning
confidence: 93%